Use of V-Y advancement flap in digital tip reconstruction after human bite: case report - Perez Carriles, Jose D.; Martinez, Marco A. Gonzalez; Rodriguez, Rosaura J. Serrano; Martinez, Abraham U. Gonzalez (International Journal of Research in Medical Sciences, 2025)
Described by Tranquilli-Leali in 1935, the V-Y advancement flap is a technique for reconstructing pulp defects. It involves the displacement of a neurovascular advancement flap. Objective were to demonstrate that the V-Y flap is a good treatment option even in complicated cases. We present the case of a 47-year-old man with diabetes who sustained a traumatic injury to the right thumb due to a human bite during a street fight. A V-Y advancement flap technique was performed for digital tip reconstruction. At 14 days postoperatively, complete flap integration was observed. This technique is ideal for addressing dorsal or transverse oblique amputations where digital tip coverage is required. The efficacy, ease, and good postoperative results make this type of surgical approach suitable for digital tip reconstruction, even in the presence of comorbidities and risk factors for infection.